Ciclo de vida de Eretris catargyrea (Staudinger, 1887), stat. rev. (Lepidoptera: Nymphalidae: Satyrinae). / Life cycle of Eretris catargyrea (Staudinger, 1887), stat. rev. (Lepidoptera: Nymphalidae: Satyrinae). - Montero Abril, Fredy; Ortiz Pérez, Maira; Viloria, Ángel L. (Anartia, 2020)
RESUMEN Presentamos las observaciones y resultados del ciclo de vida de Eretris catargyrea (Staudinger, 1887), stat. rev., una mariposa ninfálida de la subfamilia Satyrinae, endémica de los Andes de Colombia. Este estudio se realizó en el Municipio de Choachí, Cundinamarca, Colombia, a 2.300 m s.n.m. El ciclo de vida de esta especie se completó en 74 días desde la recolección del huevo hasta la emergencia del adulto. Se señala la particular coloración del huevo y su singular disposición sobre la planta huésped, Chusquea sp. (Bambusoideae: Poaceae). La larva se alimenta de láminas foliares bien desarrolladas durante las horas diurnas y se caracteriza por la forma alargada de su cabeza y la ausencia de protuberancias cefálicas o cuernos en los diferentes instares. ABSTRACT We present the observations and results of the life cycle of Eretris catargyrea (Staudinger, 1887), stat. rev., a nymphalid butterfly of the subfamily Satyrinae, endemic to the Colombian Andes. This study was carried out in the Municipality of Choachí, Cundinamarca, Colombia, at 2,300 m asl. The life cycle of this species was complete in 74 days from egg collection to adult emergence. The particular coloration of the egg and its unique placement on the host plant, Chusquea sp. (Bambusoideae: Poaceae), are pointed out. The larva feeds on well-developed leaf blades during daylight hours, and is characterized by the elongate shape of its head and the absence of cephalic protuberances or horns at different instars.